Japanese Writers and Works on Djawa Baroe: Behind the Selection of the Five Works - Anwar, Fithyani (Makassar State University, 2024)
Abstract. Literature became one of the propaganda tools of the Japanese military government during the Japanese occupation of Indonesia (1942-1945). This research focuses the object of study on four short stories and one play written by Japanese writers published in Djawa Baroe magazine (1943-1945), including